Health Needs, Health Seeking Behaviour of Interstate Migrants and Health System Response: A Case study. - R.S, Sithara; Sebastian, Ajeesh (Journal of Social Work Education and Practice, 2017)
Health needs and health seeking behaviour of interstate migrants are an area of priority because the migration is changing into a standard development within the globalized world. The increased pressure on the general public health system to produce quality health care to the guest population is often does not reach the bottom level. The researchers have conducted a cross sectional study by taking eighty sample population from West Bengal working in construction sector in Calicut district. They were asked about the health needs, health seeking behaviour and also the system’s response to that. The self-reported answers were qualitatively analysed and information is presented. The linguistic and other cultural barriers and previous experiences with the health service providers at Kerala have influenced the health seeking behaviour of the population in utilizing the services from primary health centres. They make cost benefit analysis before accessing different health care providers and often skip PHC due to the time clash. Another factor is that the chemists and private clinics are functioning at a time which is convenient to the migrant population whereas the timing of PHC functioning is a barrier in accessing the services.
Keywords: Health; Needs; Inter State Migration; Migrants; Health System; Response